Predictive factors for endoscopic recurrence after ileocolic resection for Crohn’s disease - Hale Akpınar (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Akpınar H. Predictive factors for endoscopic recurrence after ileocolic resection for Crohn’s disease. Turk J Gastroenterol 2017; 28: 241-2.